Co-constructed Documentary Film: collaboration, dialogue, and performance in researching gender and contemporary art in Vietnam. Issue 6 (18th August 2021) - Kishore, Shweta; Stiff, Andrew
ABSTRACT: How can documentary as visual research method create a relay between feminist scholarship and the goals of feminist struggle? The use of co-constructed documentary responds to the three key concerns of feminist research: the situated nature of knowledge; the critique of hierarchical knowledge; and the intention towards emancipatory action. In other words, documentary-making opens out from a "discourse of sobriety" or representation of historical truth to encompass material transformative potential not merely through representational instruments but re-organized methods, relationships, and practices which critique documentary's social relations of power. The methodological challenge and opportunity involve the re-framing of documentary participant as collaborator with a stake in decision-making and documentary construction. Taken further, this agenda complicates the notion of documentary authorship and related concepts of creative autonomy, individuality and artist "voice." In this paper, I take up these questions to argue that dialogic authoring in contemporary art theory and practice drawing upon Mikhail Bakhtin and Grant Kester) provides the theoretical foundation of an interactional concept of art generated between co-participants.